The Impact of Nurse-Led Education Programs on Patient Outcomes - Maher Mehmas Seraj Alotibi, Basmah Mshain Alharbi, Aber Mshain Alharbi, Amnah Yahya Mohammed Atiah, Abrar Jaber Mohsen Jabali, Fatimh Hussin Hantool; ‏ Ali Hussain Ali Alharbi, Amer Abdullah Amer Al Shehri, Ayed Mohammd Alzahrani, Fawziah Hadi Alanzi (Journal of International Crisis and Risk Communication Research, 2024)
Nurse-led education programs have emerged as a transformative approach in healthcare, offering tailored and patient-centered education to improve health outcomes. These programs leverage the unique position of nurses as trusted healthcare providers to bridge the gap between complex medical knowledge and patient understanding. By focusing on holistic care, skill-building, and behavior modification, nurse-led programs have demonstrated significant success in improving clinical outcomes, enhancing quality of life, and reducing healthcare costs. This paper explores the components, benefits, and measurable impacts of these programs, highlighting their critical role in chronic disease management, surgical care, and preventive health strategies.